Native pathways : American Indian culture and economic development in the twentieth century - Hosmer, Brian C., 1960-; O'Neill, Colleen M., 1961- (Book collections on Project MUSE., 2004)
"Including contributions from historians, anthropologists, and sociologists, Native Pathways offers fresh viewpoints on economic change and cultural identity in twentieth-century Native American communities."--Jacket.